Estudio del cumplimiento de los estándares de calidad para el centro de desarrollo infantil Luis Fernando Ruiz de la ciudad de Latacunga periodo 2014 - 2015 - Quimbita Loma, Ana Lucia (2015)
The present study was realized with the purpose that increasing the quality of duties that give the guaranty necessary in “Luis Fernando Luis” child center in the form that de children count with safe places, because in this way their development physical, intellectual and emotional must be very good. Into advances of the study we pretend establish parameters for reinforce the actual standards established into to refer quality for that the children’s teaching – learning must be easy and funny….